2016
DOI: 10.1021/acs.orglett.6b02243
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Regioselective C8–H Amination of 1-Naphthylamine Derivatives with Aliphatic Amines

Abstract: A simple and facile protocol for palladium-catalyzed picolinamide-directed C8-H amination of 1-naphthylamine derivatives with simple secondary aliphatic amines was developed, thereby providing a new route to 1,8-naphthalenediamine derivatives. It is noteworthy that the picolinamide moiety as a bidentate directing group may play a key role in this regioselective transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In 2016, we reported the synthesis of eight HMGA1a proteins bearing phosphorylation and methylation modifications via C-to-N sequential serine/threonine ligation. [22] In this work, HMGA1a proteins were disconnected into three fragments, which were further ligated with the STL method. It is worth mentioning that Hmb group installed at the Gly96 site can help break the secondary structure of the peptide and turns out to be important for the successful synthesis of the Glu-rich acidic tail fragment during the Fmoc-SPPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, we reported the synthesis of eight HMGA1a proteins bearing phosphorylation and methylation modifications via C-to-N sequential serine/threonine ligation. [22] In this work, HMGA1a proteins were disconnected into three fragments, which were further ligated with the STL method. It is worth mentioning that Hmb group installed at the Gly96 site can help break the secondary structure of the peptide and turns out to be important for the successful synthesis of the Glu-rich acidic tail fragment during the Fmoc-SPPS.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve more complex protein targets in convergent manner, both the C-to-N [14,19] and N-to-C [20] sequential STL have been developed, relying on the temporal protection of the N-terminus of the middle fragment and semicarbazone as the SAL ester surrogate respectively. Armed with STL, a series of proteins (acylphosphatase, [14] mucin 1 glycopeptide, [21] interleukin 25, [20] HMGA1a with phosphorylation and methylation PTMs [22] ) and cyclic peptide natural products (daptomycin, [23][24] teixobactin, [25][26][27] cyclomontanin B, [28] yunnanin C [29] ) have been synthesized over the past years. In this regard, STL can really serve as a good tool for chemical synthesis of the homogeneous HMGA1a with sites specific acetylations.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of several heteroatoms in C8 position has been described in the literature (Scheme ). Cobalt‐catalyzed alkoxylation, palladium‐catalyzed amination, as well as palladium‐catalyzed selenation and thiolation were developed …”
Section: C8‐functionalization Of Naphthalene Derivativesmentioning
confidence: 99%
“…The introduction of several heteroatoms in C8 position has been described in the literature (Scheme 12). Cobalt-catalyzed alkoxylation, [26] palladium-catalyzed amination, [27] as well as palladium-catalyzed selenation and thiolation were developed. [28] Due to the importance of the nitrile moiety in chemistry, some methods were developed to realize a palladium-catalyzed C8-cyanation with low-toxic cyanating reagents (Scheme 13).…”
Section: Bidentate Directing Groups: Picolinamide Derivativesmentioning
confidence: 99%
“…In addition, the use multidentate directing groups in the cyanation of CÀHb onds has also received growinga ttention, [16] because multidentate directing groups can more easily coordinate to ac yano source than monodentate directing groups. Recently,o ur research group reported the palladium-catalyzed CÀHc yanation reactiono fn aphthalenes.…”
Section: Introductionmentioning
confidence: 99%